Potensi Kurma Sebagai Sumber Nutrasetikal dan Pangan Fungsional - Gondokesumo, Marisca Evalina; Susilowati, Retno Wilujeng (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Dates are cultivate as a staple food in many countries, especially in the Arabian Peninsula, North Africa, and the Middle East. Dates fruits and date seeds as their by-products have nutritional and health values. It is an abundant source of carbohydrates, dietary fiber, and protein. They are high-source minerals and B complex vitamins, such as thiamine (B1), riboflavin (B2), niacin (B3), pantothenate (B5), pyridoxine (B6), and folate (B9). Based on literature studies, the fruit and seeds of dates are also rich in phytochemicals, such as phenolics, anthocyanins, carotenoids, tocopherols, tocotrienols, and phytosterols. However, date fruits and seeds have not been fully utilized as functional food ingredients with numerous potential to be developed into foods that promote health benefits. Several studies have reported the health benefits of dates in in-vitro and in-vivo conditions. Further research will provide valuable information for the potential utilization of date fruit and seeds as nutritional and functional food ingredients. This review article provides comprehensive information on the bioactive compounds and nutraceutical properties of date fruits and seeds, as well as their potential for use as functional food ingredients.